Jake baked the cake - Hennessy, B. G. (Barbara G.); Morgan, Mary, 1957- (New York : Viking Penguin, 1990)
To prepare for the wedding, Sally Price buys the rice, the best man hires a band, Mr. Fine paints a sign, and Jake bakes a magnificent cake.
Booklist
School Library Journal
Horn Book Magazine
1.7
K-3
Keywords: Weddings -- Fiction; Cakes -- Fiction; Stories in rhyme; Weddings -- Fiction; Stories in rhyme; Cake -- Fiction